ALIH KODE BAHASA INGGRIS DALAM BAHASA SALUAN - AL MAHDALI, MOH. FADEL A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT   This research entitled “ English Code Switching in Saluan Language “ is attempt to identify, analyze, and find the reason of Code Switching in Togean district society and other places in Walea Kepulauan. The method used in research is descriptive.  Hoffmann and Fishmann’s concepts are used to find out the kinds of code switching and the reason of switching code. The result of this research shows that there are two kinds of code switching, they are intra-sentential code switching and inter-sentential code switching. The reason of code switching are the speaker, listener or opponent, changing the situation because of presence of a third person, changing from formal to informal, changing of subject, and for prestigious. Keyword: Code Switching, English, Saluan Language